THEORETICAL AND METHODOLOGICAL FUNDAMENTALS OF THE ACTIVITY OF A PRACTICAL PSYCHOLOGIST IN EDUCATIONAL INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2022)
In article teoretko-methodological bases of activity of the practical psychologist in educational institutions are considered, directions of work of the practical psychologist general education are analyzed and medical institutions, the model of professional interaction of the practical psychologist with the teacher as motive force of development of pedagogical innovations s presented.